Effectiveness of an Expert System for Facilities Management in Vocational High Schools - Hade Afriansyah; Ahmad Sabandi; Nurul Widya; Amelia Putri; Indah Cahya Pratiwi; Syariatul Yardha Aisyah; Meiliza Rahma Afrizul; Sonia Putri Melani; Diego Prinanda; Syamsul Mardan (Universitas Negeri Padang, 2026)
Data-driven decision-making regarding school facilities is a crucial element of effective school governance, particularly in vocational high schools (SMK), which require efficiency and accurate information. This study aims to analyze the effectiveness of an expert system for managing facilities in vocational high schools, developed as a web-based management information system. This study employs a mixed-methods approach—combining quantitative and qualitative methods—to empirically measure the practicality of the developed product. The study subjects consist of 14 SMK principals in the city of Padang. The quantitative approach was conducted using a questionnaire as the instrument, followed by statistical analysis. Meanwhile, the qualitative approach was conducted through observation and interviews. Based on the results of the quantitative study regarding the effectiveness test, it was found that all indicators—namely usability, technical performance, security, content and information effectiveness, usage efficiency, and user satisfaction—achieved maximum scores. These findings indicate that the Expert System Platform is highly effective; however, this does not imply that the product requires no further development. Qualitative research through interviews revealed that school principals desire the addition of news channels and alumni-specific data, even though the current model has been deemed effective.